Inflammation in stroke: initial CRP levels can predict poor outcomes in endovascularly treated stroke patients - Finck, Tom; Sperl, Philipp; Hernandez-Petzsche, Moritz; Boeckh-Behrens, Tobias; Maegerlein, Christian; Wunderlich, Silke; Zimmer, Claus; Kirschke, Jan; Berndt, Maria (Frontiers in Neurology, 2023)
Background and Purpose: Inflammation has been linked to poor prognoses in cardio- and cerebrovascular conditions. Known to increase after ischemia, C-reactive protein (CRP) may serve as a surrogate for systemic inflammation and thus be a hallmark of increased tissue vulnerability. The question arises if CRP in the acute phase of ischemic stroke, prior to mechanical thrombectomy (MT), might help predict outcomes. Materials and Methods: A single-center collective of patients with large-vessel occlusion and treated via MT was analyzed in this observational case-control study. Uni- and multivariate models were designed to test the prognostic value of inflammatory markers (CRP and leukocytosis) in predicting clinical outcomes (modified Rankin Score >2) and all-cause mortality 90 days after MT. Results: A total of 676 ischemic stroke patients treated with MT were included. Of these, 313 (46.3%) showed elevated CRP levels (5mg/l) on admission. Poor clinical outcome and mortality at 90 days occurred in 113 (16.7%) and 355 (52.5%) patients and significantly more frequently when initial CRP levels were elevated [213 (64.5%) vs. 122 (42.1%), p<0.0001, and 79 (25.2%) vs. 34 (9.4%), p<0.0001, respectively]. CRP-levels were highly predictive for impaired outcomes, especially in patients with atrial fibrillation, in both, univariate and multivariate models. Interestingly, patients with initially elevated CRP-levels also showed more pronounced increases of CRP post-MT. Conclusion: Poor outcome and death occur significantly more often in stroke patients with elevated CRP levels before MT. Our findings suggest that stroke patients with atrial fibrillation and elevated inflammatory markers are of particular risk for poor outcomes.